Phenotypic characterization of lung macrophages in asthmatic patients: Overexpression of CCL17 - Staples, Karl J.; Hinks, Timothy S.C.; Ward, Jon A.; Gunn, Victoria; Smith, Caroline; Djukanović, Ratko (Journal of allergy and clinical immunology, 2012)
Studies with monocyte-derived macrophages (MDMs) and animal models have suggested a role for alternatively activated (M2) macrophages in asthmatic inflammation, but in vivo evidence for this phenotype in human asthma is lacking. To characterize the phenotype of lung macrophages from asthmatic patients in relation to disease severity and treatment. M2 biomarkers were first identified by using MDMs exposed to TH2 cytokines and then used to phenotype sputum and bronchoalveolar lavage (BAL) macrophages from 12 healthy control subjects, 12 patients with mild asthma, and 14 patients with moderate asthma and to assess the effects of corticosteroids and phosphatidylinositol 3-kinase (PI3K) inhibitors. Sputum macrophages from asthmatic patients expressed significantly more CCL17 mRNA but less CD163 than macrophages from healthy subjects. However, none of the other M2 biomarkers were differentially expressed in asthmatic patients, and ex vivo BAL cells spontaneously produced similar amounts of M2 cytokines/chemokines (IL-10, CCL17, and CCL22). CCL17 mRNA overexpression correlated weakly but significantly with sputum eosinophilia (P = .0252) and was also observed in macrophages from patients with moderate asthma treated with inhaled steroids, suggesting relative insensitivity to inhibition by corticosteroids. The PI3K inhibitor LY294002 inhibited basal CCL17 release from BAL cells and IL-4–stimulated release from MDMs. This study does not support the existence in human asthma of the full M2 phenotype described to date but points to upregulation of CCL17 in both patients with mild and those with moderate asthma, providing a further source for this ligand of CCR4+ cells that contributes to airways inflammation. CCL17 expression is corticosteroid resistant but suppressed by PI3K enzyme inhibitors.